Routine DFT testing in patients undergoing ICD implantation does not improve mortality: A systematic review and meta‐analysis - Munish Kannabhiran; Usman Mustafa; Madan Acharya; Nelson Telles; Brackett Alexandria; Pratap Reddy; Paari Dominic (Journal of Arrhythmia, 2018)
Abstract Defibrillation threshold (DFT) testing has been an integral part of implantable cardioverter‐defibrillator (ICD) implantation to confirm appropriate sensing of ventricular fibrillation and to establish an adequate safety margin for defibrillation. However, there is a lack of evidence regarding benefits of routine DFT testing. Therefore, we performed a meta‐analysis to assess its mortality benefit. We searched MEDLINE for studies comparing mortality outcomes in ICD recipients who underwent DFT testing to those who did not. For the second analysis, studies comparing outcomes in patients with high‐ vs low‐energy DFT were included. Odds ratio and standard errors were calculated, and inverse variance method in a random‐effect model was used to combine effect sizes. Fifteen studies with 10,975 subjects comparing outcomes in patients who underwent routine DFT testing during ICD implantation and those who did not were included. There was no difference in the group that did not undergo DFT testing with regards to all‐cause mortality (OR 0.935; CI 0.725‐1.207; P = 0.606), cardiac mortality (OR 0.709; CI 0.385‐1.307; P = 0.271), noncardiac mortality (OR 0.921; CI 0.701‐1.210; P = 0.554), and arrhythmic mortality (OR 1.152; CI 0.831‐1.596; P = 0.396). Percentage of successful appropriate first shocks among the two groups showed no difference. Five studies with 2278 subjects were included in the second analysis comparing patients with low DFT vs high DFT. Patients with high DFT had no significant increase in all‐cause mortality compared to patients with low DFT (OR 0.527; CI 0.034‐8.107; P = 0.646). Patients requiring higher DFT had no increased all‐cause mortality compared to patients with lower DFT. Routine DFT testing during ICD implantation does not confer any significant benefit.